LOCAL WISDOM OF MADURA FOLK SONG - Wahid Khoirul Ikhwan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The existence of Madurese folk songs has been problematic. Today's society, especially the younger generation, is no longer familiar with folk songs. People have abandoned folk songs and prefer to use digital-based games. In fact, Madurese folk songs can be used as local wisdom -based literature. The purpose of this research is to describe the values of Madurese folk songs as literacy based on local wisdom. This research uses the right approach, namely descriptive qualitative. The research design is intended to describe a situation or phenomena that occur in formal educational institutions and residents related to the values of the wisdom of the Madurese folk song as a support for BSA tourism. The instruments used are questionnaires, structured interviews, interviews, and literature review to collect data, both primary and secondary, taking into account the population of this study.